Pemboikotan Produk Pendukung Israel Berdasarkan Fatwa MUI Nomor 83 Tahun 2023 Ditinjau dari Maslahah - Amirul Nahwi Padang; Uswatun Hasanah (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This research aims to examine the boycott of products affiliated with Israel based on MUI Fatwa No. 83 of 2023 concerning the Law on Support for the Palestinian Struggle viewed from the issue of murlahah. This type of research is normative research with a conceptual approach. This research is descriptive in nature, then data is collected through document study, and data is processed using qualitative methods. The results of this research show that the boycott of Israeli products in MUI Fatwa No. 83 of 2023 in Maslahah Murlah's view is valid, this is because the boycott of Israeli products occupies the position of Maslahah Darury. By not buying Israeli products, we indirectly mean we are helping our brothers and sisters in Palestine.